Penguasaan dan Pengembangan Iptek Kemaritiman Guna Mewujudkan Indonesia Sebagai Poros Maritim Dunia - Widodo, Widodo; Bandono, Adi (Universitas Trunojoyo Madura, 2021)
Science and technology is always experiencing dynamics in the form of changes and developments. Industrial revolution 4.0. has brought new technology which is always characterized by cyber physical systems such as artificial intelligence, advance robotics, autonomous vehicles, 3d printing, virtual reality, and crypto currency, and others. The impact of the presence of these new technologies brings major and fundamental changes in various fields of life, including the maritime sector. The industrial revolution 4.0., has given rise to the phenomenon of shifting community activities which were initially carried out in the real world, now carried out in cyberspace. Everything is digital and all activities are done online with the help of internet media. In realizing the vision of the five pillars of PMD through the mastery and development of science and technology, several strategies are needed, including: (1) Building a maritime culture, through efforts: (a) the use and application of smart education technology, (b) carry out a cultural revolution or mental revolution, (c) build and expand internet network access infrastructure that is evenly distributed and reaches all regions of Indonesia. (2) Utilization of Maritime Natural Resources, with strategies, including: (a) Increasing the quantity and quality of exploration and management of natural resources classified as potential recoverable resources. (b) Increase the quantity and quality of exploration and management in the field of natural resources which are classified as potential non-recoverable resources, such as large oil and gas, minerals and mining materials. (c) Improving marine tourism management based on marine natural resources. (3) Development of Maritime Infrastructure and Connectivity, through efforts to prioritize the development of sea highways for inter-island domestic connectivity, by developing port infrastructure, and shipping and navigation safety infrastructure. (4) Improving Maritime Diplomacy, through strategies to strengthen diplomacy in the economic sector, diplomacy in the defense sector, and digital diplomacy. (5) Maritime Defense, through increasing the ability of defense equipment to defend the country's sovereignty, the territorial integrity of the Unitary State of the Republic of Indonesia, and the safety of all ethnic groups from all forms of threats.